Doing Theology in the Context of the Gift and the Promise of Nostra Aetate - Tilley, Terrence W. (Studies in Christian-Jewish Relations, 2011)
This article addresses three problems and suggests ways to address these problems. First, Christian theology has often been supersessionist, especially in Christology and Mariology. Claims about Jesus and Mary being exceptional (in different ways) often involve forms of supersessionism. I report on two theological works that attempt to be orthodoxly Catholic and to avoid supersessionism. Second, I address the conflict between affirming the irrevocable covenant God made with Israel and the universality of salvation God wrought in Jesus. I argue herein that the key problem is logical, not theological. Hence, we should not seek to resolve this problem theoretically, but to dissolve it logically in a manner analogous to the way philosophers of religion have dissolved the logical problem of evil. Third, some have suggested that a commitment to true interreligious dialogue should weaken our commitment to our own tradition. I disagree and show that interreligious dialogue can, in practice, strengthen, not weaken, our commitments to our home tradition.